Public and Private Worlds? Social History, Gender and Space - Williamson, Fiona (History compass, 2012)
Michael McKeon’s The Secret History of Domesticity is an important contribution to cultural and literary history, exploring how concepts of public and private evolved. His quest to uncover the ‘division of knowledge’ takes the reader on a journey through the low and high culture of literary genre, the history of print, art, architecture, entertainment, politics and social theory. This essay compares McKeon’s reading of public and private in light of the recent ‘spatial turn’ in social and gender history. The ‘spatial turn’ offers a close lens into the lived experience of past peoples in the same way that McKeon claims to recover the tacit knowledge embedded in the consciousness of past societies. The difference between the approaches is less about their conclusions, but their sources and methodology. Taken together they offer something that each alone cannot, a broad portrayal of a society from above and below, from the past and the present. In which case, there can be great value in placing cultural readings of the past, like Secret History, alongside social methodologies to draw together the experiences of people at all levels of society. In this article, I therefore argue for the inclusion of these contrasting and complimentary approaches to concepts of public and private within the framework of debate for Secret History.